QANUN PERSPEKTIF PLURALISME HUKUM DI INDONESIA - Yuswalina, Yuswalina (Universitas Islam Negeri Raden Fatah Palembang, 2016)
Regional Regulation (Perda) which substantially adopts Islamic law (Qanun), began to bloom again debated, and is made in conjunction with the implementation of the idea of broader regional autonomy post-centralized authoritarian Soeharto. This article explores deeply qanun (Islamic law in Aceh Province) in pluralism perspective case Indonesian Law.